Operating characteristics of a SESAM-assisted mode-locked laser oscillator with the location of the SESAM position. (January 2021) - Kwon, Seong-Hoon; Song, Dong Hoon; Kim, In-Sik; Ko, Do-Kyeong
Highlights: A mode-locked laser with the SESAM toward the middle of the cavity is designed. Operating characteristics of the mode-locked laser is studied depending on the the SESAM position. Spatial chirp is intrinsically compensated in the proposed configuration. Abstract: To establish the operating characteristics of a saturable absorber mirror (SESAM)-assisted mode-locked laser oscillator depending on the location of the SESAM, we designed a laser oscillator with the SESAM toward the middle of the cavity. We then compared it with a conventional laser oscillator that has the SESAM at the end of the cavity. The characteristics of the mode-locked pulses generated from each laser oscillator were studied along with the effective loss and wavelength-dependent loss of the SESAM, and the stability criterion against cw generation (positive group-delay dispersion (GDD) regime) and soliton dynamics (negative GDD regime). We demonstrate that no spatial chirp occurs in an output beam generated from the designed laser oscillator unlike the conventional laser oscillator when a prism pair is used for intracavity dispersion compensation. Furthermore, we applied the configuration to a Herriott-multipass cavity laser oscillator, which delivers sub-μJ pulse energy.